Blast Retrofit of Reinforced Concrete Columns - Lloyd, Alan Eric Walker (Université d'Ottawa / University of Ottawa, 2015)
Explosives place large demands on the lateral load carrying capacity of structures. If these loads are applied on columns, the high pressure transient loads from explosives can result in significant damage to the primary gravity load carrying elements. The loss of these elements, which are responsible from overall strength and stability of the structure, may cause collapse of all or parts of the structure. Therefore, it is important to mitigate the blast loads effects on columns. A comprehensive research study into the design, application, and use of different retrofit systems to mitigate damage to columns under blast loads has been undertaken. This research program, consisting of experimental testing and analytical investigation, sought out retrofits that address the strength of columns as well as those that enhance ductility are explored. Different materials and resistance mechanisms are used to increase column capacity. An experimental testing program was conducted using a shock tube to test the capacity of columns under blast loads. For this program, a total of sixteen reinforced concrete columns were constructed and the data from a further two columns from a previous study was compiled. Of these columns, a total of thirteen were retrofitted to mitigate the effects of blast. Carbon fibre reinforced polymer (CFRP) was applied to eight of the columns in the form of jacketing, longitudinal reinforcement, or the combination of the two. The other retrofits included steel prestressed confinement applied to one column, steel bracing acting as compression members applied to one column, and steel bracing acting as tension members applied to three columns. The columns were tested under incrementally increasing shock tube induced shock wave loading up to failure of the specimen or capacity of the shock tube. The performance of the retrofitted columns was compared with the control columns and against other retrofits. Quantitative comparisons of displacements and strains were made along with qualitative assessments of damage. The results indicated that all the retrofits increased capacity to the column, however, certain retrofits out performed others. The best FRP retrofit technique was found to be the combination of longitudinal and transverse FRP. The prestressed steel jacketing proved to be effective at increasing ductility capacity of the column. The compression brace retrofit was found to be effective in significantly increasing capacity of the column. The tension brace retrofits had the best performance over all the retrofits including the compression brace retrofit. The experimental data was used to validate analysis techniques to model the behaviour of the specimens. This technique reduced the columns to an equivalent single-degree-of-freedom (SDOF) system for dynamic analysis purposes. The reduction to the SDOF system was achieved by computing a resistance to lateral load and lateral displacement relationship. Each retrofit was carefully considered in this analysis including the retrofit’s possible effect on material and sectional properties as well as any force resistance mechanism that the retrofit introduces. The results of the modeling and experimental program were used to develop retrofit design guidelines. These guidelines are presented in detail in this thesis.
Keywords: Blast; Explosive; Column; Reinforced concrete; Retrofit